2013
DOI: 10.1016/j.bone.2012.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis is required for stress fracture healing in rats

Abstract: Although angiogenesis and osteogenesis are critically linked, the importance of angiogenesis for stress fracture healing is unknown. In this study, mechanical loading was used to create a non-displaced stress fracture in the adult rat forelimb. Fumagillin, an anti-angiogenic agent, was used as the water soluble analogue TNP-470 (25 mg/kg) as well as incorporated into lipid-encapsulated αvβ3 integrin targeted nanoparticles (0.25 mg/kg). In the first experiment, TNP-470 was administered daily for 5 days followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 43 publications
7
42
0
Order By: Relevance
“…Previous studies have shown that HIF-1α is critical for angiogenesis and subsequent bone formation during murine distraction osteogenesis [19, 44]. Additionally, inhibition of angiogenesis led to diminished woven bone formation following damaging mechanical loading in rats [27]. Here, a significant decrease in periosteal vascularity due to decreased HIF-1 expression was associated with less woven bone formation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Previous studies have shown that HIF-1α is critical for angiogenesis and subsequent bone formation during murine distraction osteogenesis [19, 44]. Additionally, inhibition of angiogenesis led to diminished woven bone formation following damaging mechanical loading in rats [27]. Here, a significant decrease in periosteal vascularity due to decreased HIF-1 expression was associated with less woven bone formation.…”
Section: Discussionmentioning
confidence: 86%
“…Robust expression of HIF-1α has been observed in the inflammatory cells located in the expanded periosteal region as soon as 1 day after loading, with a peak in gene expression at day 7 [22, 25]. Additionally, woven bone formation after stress fracture is preceded by increased periosteal vascularity [25, 26] and is impaired by angiogenic inhibition [27]. In contrast to fatigue loading, mechanical loading applied near physiological strain levels for fewer cycles does not produce damage, and stimulates lamellar bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…In rodent models, stress fracture healing has been shown to recapitulate the intramembranous portion of fracture repair (88), with the hallmark of stress fracture healing being the rapid formation of a hard periosteal callus of woven bone without a cartilaginous template (89). As shown in Figure 3, significant periosteal angiogenesis is associated with healing (90-91), and angiogenic inhibition attenuates the healing response (92). By quantifying gold microspheres, an immediate increase in blood flow rate was observed following the generation of a stress fracture in rats (18), consistent with reports that inflammatory markers, including IL-1, IL-6, and NOS2, are upregulated as early as 1 hour after the injury (93)(94).…”
Section: Blood Flow During Fracturementioning
confidence: 99%
“…Intramembranous ossification primarily takes place at both ends of bony callus, and new bones are formed by proliferation of periosteal osteoblasts [2, 3]. The process of fracture healing is completed as callus is remodeled, with functions of both osteoclasts and osteoblasts according to appropriate mechanical requirements [4, 5]. …”
Section: Introductionmentioning
confidence: 99%